Sie sind auf Seite 1von 5

QA 2001

II/1
Lse folgende Gleichung:

2 7x 14 17 x 2 3x
x 1 1

=
2
12
60
5
3
6

/Hauptnenner w 60

60(2 7 x ) 60(14 17 x ) 60(2 3x ) 2 60(x 1) 60 1

12
60
5
3
6

/ krzen

5 w (2 7x) (14 17x) = 12 ( 2 3x) 40 ( x 1) 10

/ Klammer

10 - 35x 14 + 17x

= 24 - 36x

- 40x + 40 10

/ Zusammenfassen

- 4 - 18x

= 54 76x

/ + 76x / + 4

58x

= 58

/ : 58

= 1

QA 2001
IV/1
Lse folgende Gleichung:
1,5x +

2(2,5x 4,5) 2(6x + 11) x 4

+3= 0
3
5
2

30 1,5x +

45x +
45x +

/ Hauptnenner w 30

30 2(2,5x 4,5) 30 2(6x + 11) 30(x 4)

+ 30 3 = 0 / Krzen
3
5
2

20(2,5x 4,5) - 12 ( 6x + 11)


50 x 90

- 72x 132

- 15 ( x -4 ) + 90
- 15x + 60 + 90

= 0 / Klammer
=0

8x - 72

=0

8x

= 72

Reutner Johannes, Hauptschule Ktzting

= 9

/ + 72
/:8

QA 2002
I/1
Lse folgende Gleichung:
17
1 2 8 7,5 13
+5
3,5
=
2x
2 3 x
6 x

/ Klammer

17
16 15 13
+ 5,5
+
=
3,5
2x
3x 18 x

/ Hauptnenner w 18x

18x 17
18x 16 18x 15 18x 13
+ 18x 5,5
+
=
18x 3,5
x
3x
18
2x

/ Krzen

153 +
57

99x -

96

+ 15x

+ 114x

= 234
= 234

177 x

- 63x
- 63x

= 177

/ Zusammenfassen
/ + 63x / - 57
/ : 177

= 1

QA 2002
IV/1
Lse folgende Gleichung:
2x + 3 3x + 8 5
1

= 2 (x 1) + 11
3
4
6
2
2x + 3 3x + 8 5

= 2x + 2 + 11,5
3
4
6

/ Hauptnenner w 12

12(2x + 3) 12(3x + 8) 12 5

=
12 2x + 12 2 + 12 11,5 / Krzen
3
4
6

4( 2x + 3) 3(3x + 8 )
ausmultiplizieren
8x + 12
-x - 12
23x
x

- 9x - 24

= 10 24x + 24 + 138

/ Klammer

= 172 24x

/ Zusammenfassen

= 172 24x

/ + 24x / + 12

= 184

/ : 23

= 8

Reutner Johannes, Hauptschule Ktzting

QA 2003
II/1
Lse folgende Gleichung:
5 5x 17
8
7x + 12 5 3 5

=
+
+
4
6x
3x
15x
2 x 6
5 5x 17
8
7x + 12 15 25

=
+
+

4
6x
3x
15x
2x 12

/ Klammer ausmultiplizieren

/ Hauptnenner w 60x

60x 5 60x (5x 17 ) 60x 8 60x (7 x + 12) 60x 15 60x 25

=
+
+

4
6x
3x
15x
2x
12

75x 10(5x 17)

= 20 w 8 + 4(7x + 12)

+ 450

75x - 50x + 170

160

+ 28x + 48

+ 450

658

- 97 x

488

25x
- 170

+ 170

122x
x

- 125x
/ + 97x/

6 80x
10x + 80
= 26,5
4
2

80x + 480 +

- 125x

/ : 122

QA 2003
III/1
Lse folgende Gleichung:
10x + 80
6 80x
1
20 x + 3 +
= 26,5
4
2

2
10x + 60 +

/ Krzen

8(6 80x )
8(10x + 80)
= 212
4
2

/ Klammer ausmultiplizieren

/ Hauptnenner w 8

/ Krzen

80x + 480 + 2(6-80x)

= 212 4(10x + 80)

/ Klammer ausmultiplizieren

80x + 480 + 12 160x

= 212 - 40x 320

/ Zusammenfassen

-80x + 492

= -108 40x

/ +80x + 108

= 40x

/ : 40

600
4

= x

Reutner Johannes, Hauptschule Ktzting

QA 2003
IV/1
Lse folgende Gleichung:
x
x
5x + 4
+ 1 = 4 10
6
4

/ Klammer ausmultiplizieren

5x + 4
6

+ 1 = x 40

/ Hauptnenner w 12

12x
12(5x + 4)
+ 12 = 12x 480
4
6

/ Krzen

3x + 12 = 12x 480 2(5x + 4)

/ Klammer ausmultiplizieren

3x + 12 = 12x 480 10x 8

/ Zusammenfassen

3x + 12 = 2x 488

/ - 2x / -12

= - 500

QA 2004
I/1
Lse folgende Gleichung:
3,5 (20,5x 315) + 107,5 = 72,5x

61,5x 410
2

71,75x 1102,5 + 107,5 = 72,5x

61,5x 410
2

143,5x 2205 + 215 = 145x 61,5x + 410

143,5x - 1990
60x
x

/ Klammer ausmultiplizieren

/ Hauptnenner w 2
/ Zusammenfassen

= 83,5x + 410

/ - 83,5x + 1990

= 2400

/ : 60

= 40

Reutner Johannes, Hauptschule Ktzting

QA 2004
III/1
Lse folgende Gleichung:
7
4
6 + x 2 6x
0,25 14 =

2x
x
4x
x

/ Klammer ausmultiplizieren

7
1
6 + x 2 6x
+ 3,5 =

2x x
x
4x

/ Hauptnenner w 4x

4x 7 4x 1
4x (6 + x ) 4x (2 6x )

+ 3,5 4x =

2x
x
x
4x

/ Krzen

14

- 4 + 14x

= 4(6 + x) (2 6x)

/Klammer ausmultiplizieren

10 + 14x

= 24 + 4x 2 + 6x

/ Zusammenfassen

10 + 14 x

= 22 + 10x

/ - 10x / -10

4x

= 12

/:4

= 3

Reutner Johannes, Hauptschule Ktzting